Lifestyle, Working Conditions, and Quality of Life Among Dentists in Kazakhstan - Azhar Syzdykova; Karlygash Toguzbayeva; Aiman Syzdykova; Danara Bekkazinova; Ainur B. Qumar; Akmaral Abikulova; Aigulsum Izekenova (International Journal of Dentistry)
Conclusion: The QoL of dentists in Kazakhstan is negatively affected by their working hours and long working experience. Measures are necessary to improve their working conditions, work schedule planning, and mental health.